2011
DOI: 10.1017/s0033291711001255
|View full text |Cite
|
Sign up to set email alerts
|

White-matter abnormalities in the right posterior hemisphere in generalized anxiety disorder: a diffusion imaging study

Abstract: We provide evidence that GAD is associated with disrupted white-matter coherence of posterior right hemisphere regions, which may partly sustain the impaired cognitive regulation of anxiety. Future diffusion imaging investigations are expected to better elucidate the communication between the parietal cortex and other right hemisphere regions in sustaining the cognitive processing of social and emotional stimuli in patients with GAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 79 publications
3
14
0
Order By: Relevance
“…Of note, a recent DTI study of GAD did not report on FA for the uncinate fasciculus, but instead used a method assessing apparent diffusion coefficient (ADC), which is equivalent to MD, for circular ROIs in each of the four major brain lobes and the corpus callosum, and found no group differences for either the frontal or temporal lobe. 42 The uncinate fasciculus findings here provide complementary support for past fMRI studies in GAD that have noted hyperactivity of the amygdala relative to healthy controls while participants are involved in processes such as implicit emotion regulation and conflict monitoring, 9 the anticipation of emotional (and non-emotional) images, 4 and viewing emotional faces. 10,11 One interpretation of the amygdala hyperactivity that has frequently been observed in GAD is that patients fail to effectively recruit prefrontal circuitry that serves to regulate amygdala responses.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Of note, a recent DTI study of GAD did not report on FA for the uncinate fasciculus, but instead used a method assessing apparent diffusion coefficient (ADC), which is equivalent to MD, for circular ROIs in each of the four major brain lobes and the corpus callosum, and found no group differences for either the frontal or temporal lobe. 42 The uncinate fasciculus findings here provide complementary support for past fMRI studies in GAD that have noted hyperactivity of the amygdala relative to healthy controls while participants are involved in processes such as implicit emotion regulation and conflict monitoring, 9 the anticipation of emotional (and non-emotional) images, 4 and viewing emotional faces. 10,11 One interpretation of the amygdala hyperactivity that has frequently been observed in GAD is that patients fail to effectively recruit prefrontal circuitry that serves to regulate amygdala responses.…”
Section: Discussionsupporting
confidence: 77%
“…The null findings for MD in the uncinate fasciculus are consistent with the only previously published MD findings for GAD. 42 Although the precise biological characteristics associated with different DTI measures are not fully known, 63 FA and MD likely quantify complementary aspects of brain microstructure. Differences in FA may reflect alterations in either myelination or axonal density, whereas MD reflects the overall density of tissue membranes irrespective of fiber orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our sample, we found overall that the left hippocampus was larger than the right; hence, our hippocampal laterality ratio indicates that participants where the right hemisphere may be approaching symmetry with the left or overtaking it in terms of size may have a more hyperactive BIS. Consistent with this, some researchers have suggested that some aspects of anxiety may be lateralized to the right hemisphere [71-73], and heightened right hemisphere activity [74], and structural changes [75] in general has been reported for clinical anxiety populations.…”
Section: Discussionmentioning
confidence: 63%
“…The interpretation of these WM differences is limited as only few studies so far reported WM volume in GAD (De Bellis et al, 2002; Strawn et al, 2013). However, while relatively little WM volume data in GAD are available, a range of diffusion tensor imaging studies already demonstrated the importance of pathological changes in WM tracts and microstructure for GAD (Brambilla et al, 2012; Tromp et al, 2012; Zhang et al, 2013), with some of these findings being related to the PFC as well (Tromp et al, 2012). The results reported here might provide another target for such investigations in the future.…”
Section: Discussionmentioning
confidence: 99%